2016
DOI: 10.1002/adfm.201602783
|View full text |Cite
|
Sign up to set email alerts
|

Spin Crossover of Yb2+ in CsCaX3 and CsSrX3 (X = Cl, Br, I) – A Guideline to Novel Halide‐Based Scintillators

Abstract: In this paper, the temperature dependence of the photoluminescence of Yb2+ doped into the halidoperovskites CsMX3 (M = Ca, Sr; X = Cl, Br, I) is presented. Yb2+ shows spin‐forbidden high‐spin (HS) and spin‐allowed low‐spin (LS) emission bands in all compounds. Upon excitation of the higher energetic LS transition, very different behaviors of the interplay of the two emissive transitions are observed. In the chlorides, the HS‐based emission becomes already dominant at higher temperatures than 50 K; in the bromi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
22
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 40 publications
(25 citation statements)
references
References 52 publications
0
22
0
Order By: Relevance
“…[174][175][176][177][178] Also anomalous thermal quenching effects often found in nanocrystals was demonstrated to be a successful strategy to achieve high relative sensitivities. [118,179,180] For the sake of completion, it is also noteworthy that divalent lanthanides such as Sm 2+ , [181][182][183] Eu 2+ , [184] Tm 2+ [185][186][187][188] and especially Yb 2+ [189][190][191][192] show potential for luminescence thermometry, although their thermal behavior is often not governed by simple Boltzmann statistics anymore, but more complex temperaturedependent excited state dynamics involving a crossover to the 4f n-1 5d 1 configuration. [193,194] Unlike the chemically more challenging examples of divalent lanthanides, Pr 3+ has also recently been introduced as an alternative, more stable luminescent thermometer with the same underlying principle of a 4f 2 -4f 1 5d 1 crossover (with eventual incorporation of thermal ionization into the conduction band).…”
Section: Introductionmentioning
confidence: 99%
“…[174][175][176][177][178] Also anomalous thermal quenching effects often found in nanocrystals was demonstrated to be a successful strategy to achieve high relative sensitivities. [118,179,180] For the sake of completion, it is also noteworthy that divalent lanthanides such as Sm 2+ , [181][182][183] Eu 2+ , [184] Tm 2+ [185][186][187][188] and especially Yb 2+ [189][190][191][192] show potential for luminescence thermometry, although their thermal behavior is often not governed by simple Boltzmann statistics anymore, but more complex temperaturedependent excited state dynamics involving a crossover to the 4f n-1 5d 1 configuration. [193,194] Unlike the chemically more challenging examples of divalent lanthanides, Pr 3+ has also recently been introduced as an alternative, more stable luminescent thermometer with the same underlying principle of a 4f 2 -4f 1 5d 1 crossover (with eventual incorporation of thermal ionization into the conduction band).…”
Section: Introductionmentioning
confidence: 99%
“…It is reported that spin-allowed transition is often observed in hosts with heavy anions or high local site symmetries. 30), 31) In CsMX 3 :Yb 2+ (M = Ca, Sr; X = Cl, Br), spin-allowed transition has been observed for CsCaBr 3 :Yb 2+ with local C 4v symmetry, whereas no spinallowed transition has been observed for CsCaCl 3 :Yb 2+ with local O h symmetry. The occurrence of spin-allowed transition has been related to the variation of the anions rather than local site symmetry for CsMX 3 :Yb 2+ (M = Ca, Sr; X = Cl, Br).…”
Section: Resultsmentioning
confidence: 99%
“…In recent years, spectroscopic properties of divalent lanthanide elements (Ln 2+ ) have been intensively studied, both experimentally [1][2][3][4][5][6] and theoretically. [7][8][9][10][11][12] However, electronic spectroscopy of divalent neodymium still remains practically an unexplored area.…”
Section: Introductionmentioning
confidence: 99%